2016
DOI: 10.3329/seajph.v5i2.28309
|View full text |Cite
|
Sign up to set email alerts
|

Obesity indices as a risk factor of skin diseases: A Case-control study conducted in Cairo, Egypt

Abstract: Overweight and obesity are two major health problems that have been recognized worldwide which affect all ages and have many negative health effects. WHO in year 2010 reported that in Egypt the prevalence of overweight among women is 76% compared to 64.5% for male while the prevalence of obesity among women is 48% compared to 22% for male. The aim of the study was to determine the most prevalent skin diseases among the studied overweight and obese patients and to examine if overweight and obesity are risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…Although with varying magnitude, the planned neighborhoods also suffer from this urban deterioration (Sutton & Fahmi, 2001). For instance, local news reported urban deterioration in high-and middle-income neighborhoods such as Zamalek and Heliopolis (Alazab, 2014;Fayed, 2019;Harby, 2018). These urban problems started initially from the rapid population growth in the city.…”
Section: Urban and Environmental Degradationmentioning
confidence: 99%
“…Although with varying magnitude, the planned neighborhoods also suffer from this urban deterioration (Sutton & Fahmi, 2001). For instance, local news reported urban deterioration in high-and middle-income neighborhoods such as Zamalek and Heliopolis (Alazab, 2014;Fayed, 2019;Harby, 2018). These urban problems started initially from the rapid population growth in the city.…”
Section: Urban and Environmental Degradationmentioning
confidence: 99%
“…The authors in Reference 5 stated that it is the fourth leading risk factor for people. Also, blood pressure and obesity are quietly closed to physical inactivity 6 . The authors showed that physical fitness can decrease mental disorder, cancer, diabetes, muscle issues, weight issues, emotional issues, and depression as well.…”
Section: Introductionmentioning
confidence: 99%